COVID-19 vaccine hesitancy among health service providers: a single centre experience from Karachi, Pakistan - Farid Bin Masood; Asma Nasim; Shahid Saleem; Aamir Mustafa Jafarey (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the views of health service providers towards coronavirus disease 2019 vaccination with Cansino, Sinovac and Sinopharm vaccines. Method: The analytical cross-sectional study was conducted at the Sindh Institute of Urology and Transplantation, Karachi, in May and June 2021, and comprised doctors, nurses, technical staff, and medical social officers. Data was collected using a questionnaire, in Urdu and English languages, assessing determinants of hesitancy. Data was analysed using SPSS 19. Results: Of the 331 subjects, 156(47%) were males and 175(53%) were females. Overall, 183(55%) subjects were aged <30 years, and 7(2%) were aged >60 years. Among the responders, 274(83%) were vaccinated, 49(15%) wanted to delay, and 8(2.4%) were outright refusers. Among the hesitant, 43(80%) were women, and 56(98%) were aged <40 years. Age, gender, occupational group and personal experience with the disease had significant correlations with vaccination status (p<0.05). Personal safety 202(74%) followed by the perception of official requirement 162(59%) were the prime reasons for getting vaccinated. No respondent cited religious inhibitions or social media as the reason behind vaccine refusal. Conclusion: A lack of trust in the safety and efficacy data of the available Chinese vaccines appeared as a factor inducing hesitancy. The resistance of younger respondents, especially trainee physicians, was a finding of concern since they form the backbone of the health system in the country. Key Words: COVID-19, Vaccine hesitancy, Health service providers.